Penurunan Nyeri Post Sectio Caesarea Melalui Teknik Relaksasi Benson dan Natural Sounds Berbasis Audio Visual - Anggrayeni Purba; Anggorowati Anggorowati; Untung Sujianto; Muflihatul Muniroh (Jurnal Keperawatan Silampari, 2021)
This study aims to research the results of the last ten years related to the effectiveness of Benson's relaxation and natural sounds against the decline in Post Sectio Caesarea pain. The method used in preparing this review literature is using several articles through nursing journals, Google Scholar, Science Direct, PubMed, Ebsco. The results of a review of several pieces of the study indicate that 78% of standard care using Benson's effective relaxation intervention in reducing post section Caesarea and 62% treatment by combining natural sounds is proven to be effective in reducing pain. In conclusion, Benson's relaxation intervention, and natural sounds are non-pharmacological therapies that are proven effective in reducing the pain of post section Caesarea. Keywords: Natural Sounds, Pain, Benson Relaxation, Caesarea Sectio